PENGARUH KERJASAMA TIM DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. FUJI SEAT INDONESIA KARAWANG - Pratiwi, Irma Ayu; Ekawaty, Novian (UNIKA Santo Thomas, 2024)
This study aims to determine how work discipline and teamwork impact the performance of employees of PT Fuji Seat Indonesia Karawang. This research applies quantitative methods with descriptive and causal associative techniques. Data was collected through observation, questionnaires, and literature studies. The data were tested for validity and reliability, coefficient of determination, multiple linear regression analysis, classical assumption test (R2), and descriptive analysis. The study population was all employees of PT Fuji Seat Indonesia Karawang, and the sample was calculated using the Slovin formula with an error rate of 5%, such as The research shows that work ethics and teamwork significantly improve employee outcomes, both partially and simultaneously. Effective teamwork characterized by good communication, trust, mutual trust, mutual support, recognition, and collective problem solving, as well as a high level of work diligence in terms of attendance, adherence to work rules and standards, vigilance, and ethical behavior, is proven to contribute to improved employee performance. This research suggests that companies should facilitate and encourage good teamwork and strictly enforce work discipline to achieve optimal employee performance. Future research can expand the scope by involving more respondents from various companies and industries, adding additional variables that may have an impact on employee performance, and using mixed methods to gain deeper insights